Development of a Novel ex vivo Nasal Epithelial Cell Model Supporting Colonization With Human Nasal Microbiota - Charles, Derald D.; Fisher, James R.; Hoskinson, Sarah M.; Medina-Colorado, Audrie A.; Shen, Yi C.; Chaaban, Mohamad R.; Widen, Steven G.; Eaves-Pyles, Tonyia D.; Maxwell, Carrie A.; Miller, Aaron L.; Popov, Vsevolod L.; Pyles, Richard B. (Frontiers in Cellular and Infection Microbiology, 2019)
The nasal mucosa provides first line defense against inhaled pathogens while creating a unique microenvironment for bacterial communities. Studying the impact of microbiota in the nasal cavity has been difficult due to limitations with current models including explant cultures, primary cells, or neoplastic cell lines. Most notably, none have been shown to support reproducible colonization by bacterial communities from human donors. Therefore, to conduct controlled studies of the human nasal ecosystem, we have developed a novel ex vivo mucosal model that supports bacterial colonization of a cultured host mucosa created by immortalized human nasal epithelial cells (NEC). For this model, immortalized NEC established from 5 male and 5 female donors were cultured with an air-interfaced, apical surface on a porous transwell membrane. NEC were grown from nasal turbinate tissues harvested from willed bodies or from discarded tissue collected during sinonasal procedures. Immortalized cells were evaluated through molecular verification of cell type, histological confirmation of tissue differentiation including formation of tight junctions, NEC multilayer viability, metabolism, physiology and imaging of the luminal surface by scanning electron microscopy. Results showed proper differentiation and multilayer formation at seven to ten days after air interface that was maintained for up to 3 weeks. The optimized mucosal cultures created an environment necessary to sustain colonization by nasal microbiomes (NMBs) that were collected from healthy volunteers, cryogenically preserved and characterized with customized quantitative polymerase chain reaction (qPCR) arrays. Polymicrobial communities of nasal bacteria associated with healthy and inflamed states were consistently reproduced in matured NEC co-cultures by transplant of NMBs from multiple community types. The cultured NMBs were stable after an initial period of bacterial replication and equilibration. This novel ex vivo culture system is the first model that supports controlled cultivation of NMBs, allowing for lab-based causation studies and further experimentation to explore the complexities of host-microbe and microbe-microbe interactions.